METHODS OF USING MODERN TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Rahmonova, Saodat (Журнал иностранных языков и лингвистики, 2023)
Multimedia technologies make it possible to make the process of teaching a foreign language attractive to the student: a bright, interesting form of providing educational material, which includes listening to audio recordings, watching videos, and films in a foreign language, and visual illustrations using Internet resources.